INVESTIGATING LOW ATTENTION SPAN IN KINDERGARTEN 3: A CASE STUDY AT SCHOOL XYZ [PENYELIDIKAN RENDAHNYA RENTANG PERHATIAN DI TAMAN KANAK-KANAK 3: SEBUAH STUDI KASUS DI SEKOLAH XYZ] - Manalu, Tania Theresia; Winardi, Yonathan (Polyglot, 2025)
The attention span of early childhood children is a critical factor in forming their developmental foundation, encompassing physical, cognitive, social, and emotional growth. Informal interviews with classroom teachers reveal that students struggle to maintain attention during instruction, often displaying behaviors such as restlessness and lack of focus immediately after the lesson begins. This thesis aims to investigate the impact of internal and external factors on the attention span among Kindergarten 3 students at Sekolah XYZ, focusing on regular classroom settings and specialized classes (music and art). This research employs a case study method by combining observations, interviews, and documentation to provide a comprehensive understanding of the issue. The findings of this research include a limited direct exploration within the classroom and the type of curriculum currently used, which are reasons for the low attention span of Kindergarten 3 students. This study highlights the novelty of tactile learning approaches to enhance attention span. To expand these findings, future research is expected to consider comparative studies across Yayasan XYZ network, investigating the impact of direct exploration and different educational approaches on the attention and learning outcomes of students in specialist classes. Abstrak bahasa Indonesia Rentang perhatian anak usia dini adalah faktor kritis dalam pembentukan dasar perkembangan mereka, mencakup pertumbuhan fisik, kognitif, sosial, dan emosional. Wawancara informal dengan guru-guru kelas mengungkapkan bahwa murid kesulitan untuk mempertahankan perhatian selama instruksi, sering menunjukkan perilaku seperti gelisah dan ketidakfokusan segera setelah pembelajaran dimulai. Penelitian ini bertujuan untuk menyelidiki dampak dari faktor internal dan eksternal terhadap rentang perhatian di kalangan murid Kindergaten 3 di Sekolah XYZ, berfokus pada setting kelas reguler dan khusus (musik dan seni). Penelitian ini menggunakan metode studi kasus dengan menggabungkan observasi, wawancara, dan dokumentasi untuk memberikan pemahaman komprehensif tentang isu tersebut. Hasil dari penelitian ini ialah eksplorasi langsung yang terbatas dalam kelas, juga jenis kurikulum yang digunakan saat ini yang menjadi alasan rendahnya rentang perhatian siswa TK 3. Penelitian ini menyoroti kebaruan dari pendekatan pembelajaran taktil untuk meningkatkan rentang perhatian. Untuk memperluas temuan ini, penelitian masa depan diharapkan mempertimbangkan studi perbandingan di seluruh jaringan Yayasan XYZ, menyelidiki dampak eksplorasi langsung dan pendekatan pendidikan yang berbeda terhadap perhatian dan hasil belajar murid di kelas-kelas khusus.